Deposition and Characterization of Tin Sulphide Thin Films by Chemical Bath Deposition Technique - Ho, Soon Min (Research India Publications, 2011)
Tin sulphide thin films were deposited onto microscope glass slides by chemical bath deposition method using Na2EDTA as a complexing agent. The main advantages of this method were low cost, low temperature and simple set-up equipments. The structural, morphological and optical properties of SnS films were studied by X-ray diffraction, atomic force microscopy, scanning electron microscopy and UV-Visible spectrophotometer, respectively. X-ray diffraction studies indicated the presence of polycrystalline nature with cubic structure. Atomic force microscopy image and scanning electron microscopy micrograph revealed that grains were uniformly distributed over the surface of substrate. Optical band gap values of direct and indirect transitions were observed to be 1.5 eV and 1.0 eV, respectively.